Anticipation and Surprises in Central Bank Interest Rate Policy : The Case of the Bundesbank. (IMF Working Papers; Working Paper ;, 1998)
Market reaction to a change in official interest rates will depend on the extent to which the change is anticipated, and on how it is interpreted as a signal of future policy. In this paper, a technique is developed to separate the anticipated and unanticipated components of such changes and is applied to estimate the response of Euro-deutsch mark interest rates to adjustments in the Bundesbank's Lombard and discount rates. The results shed light on the efficiency of this market and on the scope for policy signaling by the central bank.